Perkembangan Seni Qasidah di Desa Sei Mencirim Kecamatan Kutalimbaru - Nasution, Abdul Gani Jamora; Puspita, Anggun Dela; Balqis, Annisa; Siregar, Latifah (ANWARUL, 2023)
The study aims to find out how the qasidah group located in Sei Mencirim village maintains it's existence. This research was conducted on a qasidah group named As-Salam. The formation of the qasidah As-Salam group in the village of Sei Mencirim has existed since 2000 with 15 members. The method used in this study uses descriptive qualitative research. In dara collection is done by means of observation, interviews and documentation. Based on the data obtained, the development of the original and unsuitable qasidah group Sei Mencirim has developed well until now. In addition, in it's development, the members of the qasidah As-Salam group have their own characteristics, namely a close sense of kinship between them. The benefits of As-Salam glucoside it self are such as providing Islamic nuanced advice to the community in an activity such as recitation marriages and others. The way the qasidah As-Salam group maintains it's existence is by focusing on qasidah themes and songs with members personnel and adjusting in advance what theme will be performed so that it is right on target.